Projections and Policy Scenarios to Meet Future Global Electric Energy Needs - Tachrir, Tachrir; Lolok, Agustinus; Zulkaida, Wa Ode; Aswad, Nini H.; Fariki, La; Alwi, Saemu; Hasddin, Hasddin (International Journal of Energy Economics and Policy, 2025)
Projection and/or forecasting of future electricity production and consumption is needed to ensure its availability. The purpose of this study is to present empirical facts regarding global electricity production (supply) and consumption needs (demand) in the last 30 years (1993-2022). The second objective is to project and create policy scenarios to meet global electricity needs in the future, until 2052. Using a quantitative descriptive paradigm to explain empirical facts based on quantitative data. Data were collected from electricity production and consumption reports by Enerdata, and the European Commission during the period 1993-2022. Data analysis uses a Business-As-Usual (BAU) scenario model with the help of regression. It was found that global electricity consumption and production spread across Europe, CIS-Russia, North America, Latin America, Asia, the Pacific, Africa, and the Middle East during 1993-2022 are under each other, and show an increasing trend every year. Since 2003, Asia has had the largest electricity production and consumption. To meet global electricity needs until 2052, the policy scenario needed is the need for additional efforts from current production capacity. Asia is the largest, namely 370.05% or 12.33% per year.